Modeling human perception of orientation in altered gravity - Clark, Torin K.; Newman, Michael C.; Oman, Charles M.; Merfeld, Daniel M.; Young, Laurence R. (Frontiers in Systems Neuroscience, 2015)
Altered gravity environments, such as those experienced by astronauts, impact spatial orientation perception and can lead to spatial disorientation and sensorimotor impairment. To more fully understand and quantify the impact of altered gravity on orientation perception, several mathematical models have been proposed. The utricular shear, tangent, and the idiotropic vector models aim to predict static perception of tilt in hyper-gravity. Predictions from these prior models are compared to the available data, but are found to systematically err from the perceptions experimentally observed. Alternatively, we propose a modified utricular shear model for static tilt perception in hyper-gravity. Previous dynamic models of vestibular function and orientation perception are limited to 1 G. Specifically, they fail to predict the characteristic overestimation of roll tilt observed in hyper-gravity environments. To address this, we have proposed a modification to a previous observer-type canal otolith interaction model based upon the hypothesis that the central nervous system treats otolith stimulation in the utricular plane differently than stimulation out of the utricular plane. Here we evaluate our modified utricular shear and modified observer models in four altered gravity motion paradigms: a) static roll tilt in hyper-gravity, b) static pitch tilt in hyper-gravity, c) static roll tilt in hypo-gravity, and d) static pitch tilt in hypo-gravity. The modified models match available data in each of the conditions considered. Our static modified utricular shear model and dynamic modified observer model may be used to help quantitatively predict astronaut perception of orientation in altered gravity environments.